Effects of a diet based on inulin-rich vegetables on gut health and nutritional behavior in healthy humans. Issue 6 (24th April 2019) - Hiel, Sophie; Bindels, Laure B; Pachikian, Barbara D; Kalala, Gaetan; Broers, Valérie; Zamariola, Giorgia; Chang, Betty P I; Kambashi, Bienvenu; Rodriguez, Julie; Cani, Patrice D; Neyrinck, Audrey M; Thissen, Jean-Paul; et al.
ABSTRACT: Background: Inulin-type fructans (ITFs) are a type of fermentable dietary fiber that can confer beneficial health effects through changes in the gut microbiota. However, their effect on gut sensitivity and nutritional behavior is a matter of debate. Objective: We evaluated the impact of consuming ITF-rich vegetables daily on gut microbiota, gastro-intestinal symptoms, and food-related behavior in healthy individuals. Methods: A single group-design trial was conducted in 26 healthy individuals. During 2 wk, the participants were instructed to adhere to a controlled diet based on ITF-rich vegetables (providing a mean intake of 15 g ITF/d). Three test days were organized: before and after the nutritional intervention and 3 wk after returning to their usual diet. We assessed nutrient intake, food-related behavior, fecal microbiota composition, microbial fermentation, and gastrointestinal symptoms. Results: The major microbial modifications during the intervention were an increased proportion of the Bifidobacterium genus, a decreased level of unclassified Clostridiales, and a tendency to decrease Oxalobacteraceae . These changes were reversed 3 wk after the intervention. The volunteers showed greater satiety, a reduced desire to eat sweet, salty, and fatty food, and a trend to increase hedonic attitudes towards some inulin-rich vegetables. Only flatulence episodes were reported during the dietary intervention, whereas intestinal discomfort, inversely associated with Clostridium cluster IV and Ruminococcus callidus, was improved at the end of the intervention. Conclusions: A higher consumption of ITF-rich vegetables allows a substantial increase in well-tolerated dietary fiber, which may in turn improve food-related behavior. Moreover, it leads to beneficial modifications of the gut microbiota composition and function. This trial is registered at clinicaltrial.gov as NCT03540550.